1993
DOI: 10.1088/0022-3727/26/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Description of microwave discharges in hydrogen

Abstract: Measurements of the mass of gas enclosed in a quartz tube confining a burning hydrogen microwave plasma and the emitted intensities of atomic lines with axial or radial dependence are described. The microwave power was varied between about 450 and 1300 W, the gas pressure between 10 and 150 mbar. The experimental results are compared with numerical calculations. The simulations lead to three-dimensional distributions of electron densities, electron engines, field strengths, temperatures and gas compositions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Many investigators simulated kinetics in plasmas such as hydrogen, oxygen, and silane plasma and showed a distribution of activated species in an afterglow region. Their simulation did not deal with all activated species but with either radicals or electrons, and ions, although the plasma contains radicals, electrons, and ions.…”
Section: Theoretical Background Of Remote Hydrogen Treatmentmentioning
confidence: 99%
“…Many investigators simulated kinetics in plasmas such as hydrogen, oxygen, and silane plasma and showed a distribution of activated species in an afterglow region. Their simulation did not deal with all activated species but with either radicals or electrons, and ions, although the plasma contains radicals, electrons, and ions.…”
Section: Theoretical Background Of Remote Hydrogen Treatmentmentioning
confidence: 99%
“…There are essentially two principal frictional coefficients: F φ , for the spinning rotation of the long axis; and F θ , for the tumbling about the long axis. The observed fast and slow component relaxation times are given by 1/τ fast ) 2kT(1/F θ + 2/F φ ) and 1/τ slow ) 6kT/F θ , respectively (37).…”
Section: Methodsmentioning
confidence: 97%
“…The qualitative appearance of this signal is quite similar to that for the wild-type rod minifilaments Since a symmetric bipolar filament has no inherent dipole, we argued previously (23,24) that a dipole moment is induced by a distortion of the minifilament structure, as, for example, by flexing of the HMM portions of the monomers within the filament in the direction of the applied electric field. This can explain the large negative birefringence component of the signal that indicates a very unusual perpendicular orientation of the long filament axis with respect to the applied electric field (37). The positive birefringence signal is due to a projection of the optical axis onto this perpendicular dipole direction, as, for example, from a nonzero angle between the HMM and the minifilament axis.…”
Section: Prediction Of Coiled-coil Formation By Myosin II Rodsmentioning
confidence: 96%
“…A low-temperature plasma 17,18 of suitable characteristics can be produced, e.g., by inductive 19 and capacitive 20 rf discharges, 21 cathodic 22 and anodic 23,24 vacuum arcs, and microwave discharges. 25 The plasma parameters, together with other simulation parameters, are listed in Table I.…”
Section: Modelmentioning
confidence: 99%